Enhancing Islamic Jurisprudence Learning through Addie-Based Game Development: An Empirical Study - Yudik Pradana; Nur Aisyah (Yayasan Avicenna, 2024)
This study aims to improve the quality of fiqh learning at the senior high school level through the development of game-based learning media (Game-Based Learning/GBL) with the ADDIE model approach (Analysis, Design, Development, Implementation, Evaluation). The method used is a qualitative case study type approach, with teachers and students as subjects. Data collection techniques include interviews, observations, and documentation, which are analyzed interactively to ensure the validity of the findings. The results of the study indicate that the application of the ADDIE model in the development of GBL media can significantly improve the understanding of fiqh concepts, as indicated by an increase in student scores from 45% to 70% which exceeds the KKM. In addition, student motivation and participation increased, as seen from the increase in their attendance and active involvement in the challenge and simulation-based learning process. The implications of these findings confirm that the development of game-based media with the ADDIE systematic approach can be an innovative solution to overcome students' boredom and disinterest in fiqh material which was previously considered abstract and monotonous. Therefore, this study recommends the widespread implementation of ADDIE-based GBL as an effective pedagogical strategy in contemporary Islamic education.